A sustainable approach to helminth eggs concentrations removal in sewage sludge from biological wastewater treatment: A Brazilian case study - Guilherme Sgobbi Zagui; Lisandro Simão; Danielma Silva Maia; Brisa Maria Fregonesi; Karina Aparecida Abreu Tonani; Marília Vasconcellos Agnesini; Cristina Filomena Pereira Rosa Paschoalato; Susana Inés Segura-Muñoz (Waste Management Bulletin)
Sewage sludge can be used as fertilizer in agriculture, representing an environmentally and economically advantageous alternative to disposal in landfills and incinerators, however helminth eggs compromises its destination. In this study, we evaluated helminth eggs in raw and treated sewage sludge after thermal drying in an agricultural greenhouse, from two wastewater treatment plants (namely WWTP-A and WWTP-B), in intention of verifying a low-cost treatment technology to obtain treated sewage sludge for agricultural purposes. Helminths eggs of Hymenolepis diminuta and Ascaris sp were the most frequent. In the sludge from WWTP-A the mean concentration of helminth eggs, respectively, was 3.49 ± 1.45 and 1.01 ± 1.13 eggs/g TS in the raw and treated sludge (p = 0.0382). In WWTP-B, the mean concentration of helminth eggs was 8.14 ± 1.28 and 2.33 ± 3.81 eggs/g TS, respectively, in the raw and treated sludge (p = 0.0495). The maximum percentages of egg removal were 93.81 % in WWTP-A and 98.80 % in WWTP-B. No viable eggs were detected in treated sewage sludge, indicating that the biosolid could be classified as Class A under legal parasitological parameters, allowing for extensive use in agricultural crops, which represents a sustainable alternative for the disposal of sewage sludge.